A systematic review of resource habitat taboos and human health outcomes in the context of global environmental change. Issue 2 (1st October 2016) - Angsongna, Alexander; Ato Armah, Frederick; Boamah, Sheila; Hambati, Herbert; Luginaah, Isaac; Chuenpagdee, Ratana; Campbell, Gwyn
ABSTRACT: The dependence of humans on the ecosystem services that natural resources provide is absolute. The need for social taboos as frameworks for governing natural resource abstraction is gaining widespread recognition especially within the context of climate change. However, the complex relationship between resource and habitat taboos (RHTs) and human health is not entirely understood. We conducted a systematic review of existing studies of the association between RHTs and human health outcomes, focusing on the best evidence available. We searched JSTOR, SocINDEX, Greenfile and Academic Search Complete databases from 1970 to July 2015; and also searched the reference lists of reviews and relevant articles. About 779 studies and data from 26 studies were eligible for the analysis. Only 9 out of 26 studies clearly linked RHTs to human health. Overall, nine taboos, spatial, temporal, gear, method, effort, catch, species-specific, life history and segment, were covered by the empirical studies. This systematic review provides new evidence of relationships between RHTs and human health outcomes. Several methodological limitations were identified in the empirical material. The findings suggest the need for context-specific conservation policies to reduce erosion of RHTs in order to sustain human health in the face of climate change.